1997
DOI: 10.1037/0894-4105.11.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Motor recovery after stroke depends on intact sustained attention: A 2-year follow-up study.

Abstract: The functional recovery of 47 right-brain-damaged stroke patients was studied over a 2-year period. The researchers hypothesized that sustained attention capacity should predict the degree of motor and functional recovery over this period because of a proposed privileged role of sustained attention in learning-based recovery of function. As predicted, significant correlations were found between sustained attention capacity at 2 months and functional status (including the Barthel Index) at 2 years. This relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
130
2
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(144 citation statements)
references
References 32 publications
9
130
2
3
Order By: Relevance
“…Attention, including fluctuations in attention over time, may therefore have critical implications for the treatment of language deficits in aphasia. There is already evidence that good attention in stroke patients is predictive of overall functional recovery (Mysiw, Beegan, & Gatens, 1989), as well as motor recovery (Robertson, Ridgeway, Greenfield, & Parr, 1997). Additionally, there is evidence that successful language rehabilitation may involve changes in attention-related neural networks, in particular the DMN (Marcotte, Perlbarg, Marrelec, Benali, & Ansaldo, 2013).…”
Section: Implications Of Attention For Aphasia Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Attention, including fluctuations in attention over time, may therefore have critical implications for the treatment of language deficits in aphasia. There is already evidence that good attention in stroke patients is predictive of overall functional recovery (Mysiw, Beegan, & Gatens, 1989), as well as motor recovery (Robertson, Ridgeway, Greenfield, & Parr, 1997). Additionally, there is evidence that successful language rehabilitation may involve changes in attention-related neural networks, in particular the DMN (Marcotte, Perlbarg, Marrelec, Benali, & Ansaldo, 2013).…”
Section: Implications Of Attention For Aphasia Treatmentmentioning
confidence: 99%
“…Not only has attention been shown to be predictive of long-term functional recovery after stroke (Mysiw, Beegan, & Gatens, 1989;Robertson, Ridgeway, Greenfield, & Parr, 1997), evidence from the aphasia literature has also suggested that cognitive abilities such as attention may successfully predict language therapy outcomes (Lambon Ralph, Snell, Most models frame attention as a domain-general resource that may be drawn on for a variety of tasks, both linguistic and non-linguistic (e.g. Posner & Petersen, 1990;Mirsky, Anthony, Duncan, Ahearn, & Kellam, 1991;Petersen & Posner, 2012;Cohen, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Impaired attention can reduce cognitive productivity when other cognitive functions are intact 11 and is key to learning motor skills. 12 Robertson et al 13 reported that sustained attention 2 months after stroke predicts functional recovery at 2 years. Nys 9 found cognitive impairment 1 week after stroke predicts quality of life 6 months after stroke (Stroke Impact Scale), with visual hemi-inattention contributing significantly.…”
mentioning
confidence: 99%
“…Specifically, the ability to sustain attention to a tone counting task (a validated measure of sustained attention which is related to right frontal function) at two months post-stroke predicted not only everyday life function 2 years later, but also the functional dexterity of the left hand in a pegboard task (Robertson, et al, 1997).…”
mentioning
confidence: 99%